Light Conduction Capability of Different Light-Transmitting - Saied Mostafa Moazzami; Reza Kazemi; Maliheh Alami; Ebrahim Attaran; Michael Mehhary; Majid Sarmad; Heydar Shahrokh (Mashhad University of Medical Sciences, 2012)
Introduction: Application of light transmitting posts to restore greatly damaged endodontically treated teeth has been increased. It is suspected that light intensity decreases as it passes throughout different materials. This can reduce the degree of conversion required for adequate bond strength throughout the length of these posts. The objective of this study was to evaluate the amount of light intensity reduction after passing through different depths of FRC posts. Methods: Four groups of five extracted human central incisors were prepared to cement four types of FRC posts with Panavia F 2 resin cement. The apical end of the posts were exposed by sectioning with a diamond disk and then polished. The light intensity measurement was performed using a micro-voltmeter in 8 points or depths with 2mm intervals beginning from the apical depth of 16mm up to a coronal depth of 6mm. Two different output light intensities [HIP (High Intensity Program) and LOP (Low Intensity Program)] were evaluated. Results: Statistical analysis showed significant differences in light intensity at various depths between 6 and 16mm in all groups. These reductions were linear in all specimens; however, the rate of reduction was dissimilar among different FRC posts. HIP and LOP light exposure modes had not the same rate of light reduction. Conclusion: Light intensity decreased dramatically after passing through different depths of FRC posts. None of the posts had sufficient enough light transmission for satisfactory polymerization at the apical and middle levels.